Institutional Constraints in Media Convergence: Policy Reforms and Social-Ideological Education Dynamics in China’s County-Level Broadcasting - Dong, Yang (European Journal of Social Science Education and Research, 2026)
This study explores the complexities of media convergence reforms within China’s county-level radio and television stations. Utilizing Institution Innovation Theory, it examines the reform approaches of Pizhou Radio-TV Station, a pioneer in this movement. Employing a qualitative case study approach with data gathered through participant observation and in-depth interviews, this research analyzes the administrative, technological, and commercial adaptations undertaken by the station. The findings reveal that reforms are not purely market-driven but represent a compromise between political mandates and survival needs. Consequently, the study proposes the concept of Institution Derivation to explain how local media innovate within the strict constraints of the socialist four-level media system. This theoretical contribution suggests that while local media can break path dependence to a degree, they ultimately derive their operational logic from the overarching state-owned framework, resulting in a unique semi-enterprise, semi-institution equilibrium.
Keywords: Digital Transformation; Media Convergence; Institution Derivation; Institution Innovation; Local Governance; Party-State System; State-Market Relations